2013
DOI: 10.3855/jidc.3458
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Moraxella spp. strains recovered from infectious bovine keratoconjunctivitis cases in Uruguay

Abstract: Background: Infectious bovine keratoconjunctivitis (IBK) is the most common ocular disease that affects cattle throughout the world and it has a very significant economic impact. IBK is caused by members of the genus Moraxella and therapeutic and preventive measures have shown limited success. Vaccines, most of them chemically inactivated bacterins, generally induce a limited protection. Methodology: In this study, the genetic diversity of Uruguayan clinical Moraxella bovis and Moraxella bovoculi isolates was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 18 publications
2
15
0
1
Order By: Relevance
“…Mundialmente são escassos os estudos a respeito da ocorrência de M. bovoculi. Na América do Sul, apenas Sossa et al (2010) relatam surtos de CI causados por M. bovoculi em bovinos.…”
Section: Discussionunclassified
“…Mundialmente são escassos os estudos a respeito da ocorrência de M. bovoculi. Na América do Sul, apenas Sossa et al (2010) relatam surtos de CI causados por M. bovoculi em bovinos.…”
Section: Discussionunclassified
“…in other countries but have not examined these on a herd or individual animal level. 27 It was observed in the current study that M. bovoculi was the only Moraxella sp. isolated from the majority of case submissions, when evaluated at either the herd or individual level.…”
Section: Discussionmentioning
confidence: 88%
“…Interestingly, both M. bovoculi and M. ovis strains were isolated from the same sheep eye lesion. Since the first description of M. bovoculi, studies from different parts of the world reported its isolation from eye lesions in cattle Libardoni et al, 2012;Sosa and Zunino, 2013); however, the exact role played by this species in the pathogenesis of IK is still not fully understood. Similar results were found for South American strains showing a hyper conservation of the MbxA-3 0 region .…”
Section: Discussionmentioning
confidence: 99%
“…Although early investigations proposed M. ovis, bacterium involved in sheep eye disease, might be the case (Elad et al, 1988), more recent investigations isolated and identified M. bovoculi in cattle lesions Libardoni et al, 2012;Sosa and Zunino, 2013).…”
Section: Introductionmentioning
confidence: 97%